Investigating the Drinking Water Quality and Associated Health Risks in Metropolis Area of Pakistan - Sohail, Muhammad Tayyab; Ehsan, Muhsan; Riaz, Sidra; Elkaeed, Eslam B.; Awwad, Nasser S.; Ibrahium, Hala A. (Frontiers in Materials, 2022)
Water is the basic need of human being with no substitute of it. This research aims to investigate the drinking water quality and dissociated risk calculations of metropolis area in Pakistan. The present study was based on public awareness toward water quality and real situation of water quality of filtration plants in Islamabad. A questionnaire was designed with the help existing literature about public awareness on water quality. In present study 450 completed questionnaire were collected and analyze with help of statistical tools. To investigate the real situation of water quality in study area 32 samples were analyzed from installed filtration plants. The results presented that electrical arsenic, conductivity (EC) and alkalinity were higher and 26 samples were found unsafe for drinking under poor water quality (WQI > 100). Hazard index of arsenic was found < 1 in adults (7.03E+01) and children (1.06E+02) at Islamabad. To check the Microbiological situation were included as well for health risk assessment. There is a need of comprehensive management for the sustainability of filtration plants. Public satisfaction can be enhanced by dissemination the significant importance of water quality in annual government report to the public via local social media, print media, and television.